(untitled) (Jóvenes en la Ciencia, 2025)
This work presents the development of a portable micro-spectrometer for visible light analysis, designed for scientific and educational applications. To achieve this purpose, the Hamamatsu C12880MA spectral sensor and an STM32 microcontroller were used. The sensor was controlled using digital signals (START, CLK, and TRG), while its analog output (VIDEO) was conditioned with a resistive divider and digitized using the microcontroller’s ADC. The results obtained validated the spectral behavior of the system using LEDs of different colors, identifying intensity peaks that match the characteristic wavelengths of each light source. Tests conducted with Hibiscus sabdariffa (hibiscus) films revealed absorption patterns consistent with their nonlinear optical properties. The prototype demonstrated the feasibility of integrating compact spectral sensors with general-purpose microcontrollers, resulting in a functional, accessible system with potential for use in scientific and educational settings for portable spectral analysis at a reduced cost compared to other commercial systems.